Genetics of pathogenicity in Pyrenophora leaf diseases of barley - Campbell, Graham F. (Graham Findlay) (Stellenbosch : Stellenbosch University, 2012)
Dissertation (PhD(Agric)) -- University of Stellenbosch, 2001.